Upaya Meningkatkan Kompetensi Pedagodi Guru dalam Melaksanakan Pembelajaran melalui Supervisi Akademik di UPT SMP Negeri 1 Ambarawa Tahun 2021 - Rahmanto, Rahmanto (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The objective of this study is to improve teacher competency in implementing learning through academic supervision. This research is a school action research using an instrument used to observe teachers in carrying out learning, the overall results of the study were analyzed by using quantitative analyses and categorized into very good, good, sufficient, less and very poor categories. Respondents of this study were teachers of UPT SMP Negeri 1 Ambarawa who received the category, very poor, lacking and sufficient. The results of academic supervision in the odd semester of the 2020/2021 school year were obtained as many as 20 people consisting of 5 males and 15 females. This research consists of three cycles where each cycle uses the stages of planning, implementation / observation, evaluation and reflection. The results showed an increase in the ability of teachers to carry out learning in each cycle. The score of the teacher's ability to carry out learning before treatment was 1689; in cycle 1 a score of 2006 was obtained, in cycle 2 a score of 2277 was obtained and at cycle of 3 was obtaineda score of 2437. This indicates an increase in teachers’ competencies in implementing learning in each cycle. The composition of teachers’ competencies that reached the good and very good categories also experienced an increase in each cycle. Before treatment 0%, in the first cycle to 25%, in the second cycle to 55% and in the third cycle to 80%. From these results, it can be concluded that using academic supervision can improve teachers’competencies in carrying out learning.